Clinical characteristics and prognostic implications in patients with HER2-low breast cancer undergoing neoadjuvant chemotherapy: a retrospective cohort study - Ang Zheng; Junlin He; Muyao Li; Fan Yao; Feng Jin; Bo Chen; Xin Wang (The Lancet Regional Health. Western Pacific)
Background: HER2-low breast cancer represents a distinct biological subtype, and its clinical characteristics and prognostic outcomes require further exploration. This study aimed to investigate disparities in short- and long-term outcomes between HER2-0 and HER2-low breast cancer patients undergoing neoadjuvant chemotherapy (NAC) in a Chinese cohort. Methods: This retrospective multicenter cohort study included 711 breast cancer patients diagnosed between 2016 and 2020 in four tertiary hospitals in China. Participants were categorised into HER2-0 and HER2-low subgroups based on immunohistochemical analysis. Logistic and Cox regression analyses, incorporating propensity score-based inverse probability of treatment weighting (IPTW), were used to evaluate treatment outcomes, including real-world overall survival (rwOS), breast pathological complete response (bpCR), and objective response rate (ORR) at 24 weeks. Findings: Out of 303 patients included in the final analysis, 213 were classified as HER2-low and 90 as HER2-0. The majority were hormone receptor (HR)-positive, with varying TNM stages, Ki-67 expression levels, and menopausal status. Inclusion criteria were based on neoadjuvant chemotherapy treatment and immunohistochemistry results. The overall rwOS rate for all patients was 86.1% (HER2-low: 87.3% vs. HER2-0: 83.3%). Kaplan-Meier survival curves showed no significant difference in rwOS between the HER2-low and HER2-0 groups before or after applying the IPTW method (log-rank P = 0.17, IPTW-weighted log-rank P = 0.45). Multivariate Cox regression analysis confirmed no significant difference in rwOS between the groups (IPTW-adjusted hazard ratio [HR]: 1.60; 95% confidence interval [CI]: 0.78–3.31). For breast pathological complete response (bpCR), 45 patients (21.1%) in the HER2-low group achieved bpCR compared to 16 patients (17.8%) in the HER2-0 group (adjusted odds ratio [OR]: 1.26; 95% CI: 0.6–2.75). Similarly, no significant difference was observed in the odds of bpCR between the groups when adjusted using IPTW (OR: 1.08; 95% CI: 0.72–1.64). Objective response rates (ORR) at 24 weeks were also comparable, with 137 patients (57.4%) in the HER2-low group and 61 patients (67.8%) in the HER2-0 group achieving a response. The IPTW-adjusted OR for ORR was 1.1 (95% CI: 0.77–1.57). Subgroup analysis revealed that in HR-negative patients, the HER2-low group exhibited significantly better outcomes compared to the HER2-0 group, with an rwOS HR of 0.42 (95% CI: 0.23–0.77; P < 0.001) and bpCR odds of 2.6 (95% CI: 1.14–6.29; P = 0.027). Conversely, among HR-positive patients, HER2-0 patients had a better rwOS than HER2-low patients (P < 0.001). Interpretation: HER2-low breast cancer should be considered a distinct subtype with differing outcomes based on hormone receptor (HR) status. HR-negative patients with HER2-low tumors showed better overall survival and response rates compared to HER2-0 patients, suggesting enhanced chemotherapy sensitivity. Conversely, HR-positive HER2-0 patients had better survival, indicating potential treatment resistance in HER2-low HR-positive cases. These findings highlight the need for tailored treatment strategies for HER2-low breast cancer, especially for HR-positive patients, and suggest potential benefits from novel therapies like antibody-drug conjugates (ADCs).